The distribution of sediment bacterial community in mangroves across China was governed by geographic location and eutrophication. (March 2019) - Tong, Tianli; Li, Ruili; Wu, Sijie; Xie, Shuguang
Abstract: Bacterial community is an important component of mangrove ecosystem and can participate in the cycling of elements and promote plant growth. However, the biogeographic distribution pattern of mangrove bacterial community and the associated factors remain poorly known. The present study explored the biogeographic distribution of sediment bacterial community in six mangroves across China. At each mangrove, sediments were collected from both Avicennia marina -planted zones and intertidal mudflats. The community abundance, richness, diversity and structure of sediment bacteria differed greatly among mangrove wetlands. Plantation showed a positive influence on sediment bacterial abundance, richness and diversity. Proteobacteria was the largest bacterial phylum in sediments. The biogeographic distribution of bacterial community in mangroves across China was driven by the variables associated with the wetland trophic status as well as other physicochemical factors (e.g., salinity). Highlights: The biogeographic distribution of mangrove bacteria across China was studied. Geographic location had a considerable impact on mangrove bacterial community. Plantation showed a positive effect on bacterial abundance, richness and diversity. Mangrove trophic status influenced mangrove bacterial community.